2014
DOI: 10.3109/09638288.2014.943844
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences with intrathecal baclofen as a treatment for spasticity – a pilot study

Abstract: Patients stated that they were highly satisfied with the ITB treatment. However, the patients identified several areas that could be improved. Specifically, the patients wanted more information about the different steps in the treatment process and what to expect from ITB treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Guillaume et al [33], for example, reported good or very good levels of overall physician satisfaction with ITB Therapy for almost 90% of patients, and similar opinions from a nursing perspective can be found in Staal et al [34]. Also the patients themselves express high levels of satisfaction when asked directly, as described for example by Vender et al [35], who invited patients to complete a questionnaire, or Gunnarsson and Samuelsson [36], who collected qualitative data from longterm ITB users in face-to-face interviews.…”
Section: Discussionmentioning
confidence: 61%
“…Guillaume et al [33], for example, reported good or very good levels of overall physician satisfaction with ITB Therapy for almost 90% of patients, and similar opinions from a nursing perspective can be found in Staal et al [34]. Also the patients themselves express high levels of satisfaction when asked directly, as described for example by Vender et al [35], who invited patients to complete a questionnaire, or Gunnarsson and Samuelsson [36], who collected qualitative data from longterm ITB users in face-to-face interviews.…”
Section: Discussionmentioning
confidence: 61%
“…With longer trial duration, patients have more therapy sessions to assess activities of daily living and functional mobility at different doses in a supervised setting. In the article by Gunnarrsson and Samuelsson [9], patients expressed frustration with the dose titration process and the time needed to see full effects after pump implantation compared with how they felt during the successful bolus trial. A continuous trial allows the early effective dose to be determined more quickly, potentially reducing the number of outpatient visits needed to obtain the same beneficial effects.…”
Section: Discussionmentioning
confidence: 97%
“…Gunnarrsson and Samuelsson [9] interviewed 14 patients regarding their experience with ITB bolus trials subsequent to pump implantation. Although patients were pleased with the reduction in spasticity after a bolus trial, they believed that extensive evaluations regarding changes in physical activity during the trial were lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, baclofen failed to regulate TLR4-induced TNF-α expression in PBMCs from RR-MS subjects. This is significant as intrathecal administration of baclofen can be used to treat spasticity in MS, in addition to spinal cord injury, cerebral palsy, and acquired brain injury ( Gunnarsson and Samuelsson, 2015 ). Furthermore, there is evidence of a loss of GABAergic neurons at lesion sites in post-mortem MS brain ( Redondo et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence pointing to the key role of GABA receptors in neuroinflammation ( Ziegler et al, 1980 ; Tyagi et al, 2015 ), and recent reports has identified that modulation of the GABAergic system occurs in MS ( Han et al, 2008 ; Carmans et al, 2013 ). Indeed, GABA insufficiency has been identified in MS patients ( Demakova et al, 2003 ), while intrathecal administration of the GABA B receptor agonist, baclofen, is used as a treatment strategy to control spasticity in patients with MS ( Gunnarsson and Samuelsson, 2015 ). Furthermore, enhancing endogenous GABA via administration of the GABA-degrading enzyme GABA-transaminase (GABA-T), has been shown to be protective in an experimental autoimmune encephalomyelitis (EAE) mouse model ( Carmans et al, 2013 ), indicating that increasing endogenous GABA also has therapeutic potential in the murine model of MS.…”
Section: Introductionmentioning
confidence: 99%